Likelihood of persistent carriage of carbapenem-resistant Acinetobacter baumannii on readmission in previously identified carriers. (5th August 2019) - Nutman, Amir; Lerner, Anat; Fallach, Noga; Schwartz, David; Carmeli, Yehuda
Abstract: Patients with carbapenem-resistant Acinetobacter baumannii- positive clinical cultures during a prior hospitalization were screened using high sensitivity methods upon first readmission. Of 38 patients, 31.6% screened positive; 42% screened positive within 2 months from discharge, and 14% screened positive more than 5 months from discharge. Carriage was persistent up to 285 days.